Nilai Peduli Sosial Dan Nilai Cinta Tanah Air Dalam Film Jembatan Pensil Produksi Grahandhika Visual - Luthfia Muqimatussunnah; Ika Ari Pratiwi; Su’ad Su’ad (Departement of Mathematics Education, 2023)
Character values ​​are values ​​that are instilled in the character education of elementary school children as an effort to realize national education goals. Film is one of the media that can influence the character values ​​of children or each individual. This study aims to analyze the intrinsic structure of the film Jembatan Lilin, the value of social care and love for the homeland contained in the film Jembatan Pensil, produced by Grahandhika Visual. The type of research used in this study is a qualitative research with a descriptive approach. The data analysis that will be used is descriptive qualitative data analysis, namely data reduction, data presentation, and data verification. Data collection techniques in this research use documentation techniques and refer to records that are sourced from valid data. The research results in the film